2005
DOI: 10.1007/s10350-005-0133-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Impact of Sterilized Disease and Minimal Residual Disease After Preoperative Radiochemotherapy for Rectal Cancer

Abstract: After preoperative therapy, the sterilized disease shows an excellent prognosis. The minimal residual disease has an important numeric incidence. Its outcome is different, with a not-negligible risk of distant recurrence. The minimal residual disease has a much better prognosis in comparison with the gross residual disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 34 publications
2
44
0
2
Order By: Relevance
“…On the other hand, tumor regression was associated with local recurrence (389 patients; refs. 4,8,27,28), overall survival (247 patients; refs. 8,29), or disease-free survival (270 patients; refs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tumor regression was associated with local recurrence (389 patients; refs. 4,8,27,28), overall survival (247 patients; refs. 8,29), or disease-free survival (270 patients; refs.…”
Section: Discussionmentioning
confidence: 99%
“…TRG has been shown to provide valuable prognostic information in patients with carcinomas of the breast, stomach, oesophagus and colorectum who have been treated with neoadjuvant chemotherapy and serves as a morphological marker to guide further treatment after surgery. [101][102][103][104][105] The applicability of several well-known and widely used systems for TRG has been considered for pelvic gynaecological carcinomas. Some of the systems that are used for breast carcinoma are unduly complex and include the separate assessment of both the primary tumour and involved lymph nodes.…”
Section: Carcinosarcoma Subtypesmentioning
confidence: 99%
“…Recent studies have revealed that pathological CR and greater than 95% pathological response groups achieve a significantly improved overall survival and recurrence-free survival when compared with less than 95% pathological response groups (Ruo et al, 2002;Guillem et al, 2005). Therefore, we divided the cases into two groups: Dworak grades 1 and 2, and grades 3 and 4 (Gavioli et al, 2005). The latter were considered as responders to CRT.…”
Section: Pathological Response To Crtmentioning
confidence: 99%